Global burden, subtype, risk factors and etiological analysis of enteric infections from 1990-2021: population based study - Zhang, Youao; Zhang, Yuran; Chen, Zhifeng; Jia, Zixuan; Yu, Yulan; Wang, Jieyan; Liang, Hui (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundEnteric infections represent a prevalent global health issue and contribute significantly to the global disease burden. This study aims to investigate the patterns and trends of enteric infections from 1990 to 2021, providing valuable insights for health policy formulation, medical resource allocation, and the optimization of patient management plans.MethodsWe analyzed the Global Burden of Disease (GBD) 2021 for 21 regions and 204 countries to understand better the health burden using prevalence, incidence, mortality, and disability-adjusted life years (DALYs), subtype, risk factors, and etiology. We tested correlations with the Socio-demographic Index (SDI), and using decomposition analysis to dissect the reasons behind changes in epidemiological indicators of the disease.ResultsIn 2021, the age-standardized rates of prevalence, incidence, deaths, and DALYs per 100,000 population for enteric infections were 879.58, 577.21, 17.83, and 1020.15, respectively. Compared to 1990, these rates exhibited -0.18, -0.12, -0.73, and -0.72 changes. Gender and age analyses revealed a higher burden among females, those under 15 years old, and the elderly. Regions with low SDI had higher epidemiological indicators. The burden of Typhoid fever declines in high-development regions. Unsafe water sources were identified as the primary risk factor globally in both 1990 and 2021. Rotavirus was the leading cause of deaths and DALYs.ConclusionThis study highlights the complex epidemiological landscape of enteric infections, revealing variations in burden, risk factors, and etiological characteristics across age, gender, and geographical regions. It underscores the urgent need for healthcare professionals and policymakers to develop innovative prevention and healthcare strategies based on the current and evolving burden of enteric infections, to alleviate the global disease burden.